2010
DOI: 10.1002/cphc.200900983
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Ionic Liquid Confined in Porous Silica Matrix

Abstract: Porous silica matrices of different pore sizes with confined ionic liquid (1-butyl-3-methylimidazolium hexafluorophosphate) [BMIM] [PF(6)] were prepared by sol-gel technique using a tetraethyl orthosilicate (TEOS) precursor with an aim to study the changes in physico-chemical properties of ionic liquid on confinement. It is found that on confinement 1) melting point decreases, 2) fluorescence spectra shows a red shift and 3) the vibrational bands are affected particularly those of imadazolium ring, which inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 60 publications
6
79
1
1
Order By: Relevance
“…In our earlier experimental and theoretical studies on [BMIM][PF 6 ], we found that the cation ring gets weakly attached to the silica gel surface oxygen leading to changes in melting point, fluorescence, and vibrational bands [25]. It may be noted that all the studies listed above including our study [18][19][20][21][22][23][24][25] were on ILs with small anions. More recently, we have studied the IL with large anion size [BMIM][OcSO 4 ] and have proposed a phenomenological model to qualitatively account for the anion size dependence of melting point depression [14].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…In our earlier experimental and theoretical studies on [BMIM][PF 6 ], we found that the cation ring gets weakly attached to the silica gel surface oxygen leading to changes in melting point, fluorescence, and vibrational bands [25]. It may be noted that all the studies listed above including our study [18][19][20][21][22][23][24][25] were on ILs with small anions. More recently, we have studied the IL with large anion size [BMIM][OcSO 4 ] and have proposed a phenomenological model to qualitatively account for the anion size dependence of melting point depression [14].…”
Section: Introductionmentioning
confidence: 55%
“…Most studies of ILs in confined geometry are focused on the imidazolium-based cations [19][20][21][22][23][24]. In our earlier experimental and theoretical studies on [BMIM][PF 6 ], we found that the cation ring gets weakly attached to the silica gel surface oxygen leading to changes in melting point, fluorescence, and vibrational bands [25]. It may be noted that all the studies listed above including our study [18][19][20][21][22][23][24][25] were on ILs with small anions.…”
Section: Introductionmentioning
confidence: 60%
“…As reaction media, the application of ILs for a wide variety of synthetic processes is an area of intensive research. Apart from these important applications, recently, ILs in confined geometry 14,15 attracted attention along with synthesis 16 , as reaction media 17 and effect of salts on IL 18 . ILs are also being used in variety of applications viz.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for the IL/Hal/MCC-4 composite, lower characteristic phase-transition temperatures were observed compared to those for the composites without polymer ( Table 3 ). It should be noted that the confinement effect is caused by the strong interaction of the ionic liquid with the inner surface of halloysite nanotubes [ 6 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%